Reflections on 21st Century Human Habitats in India
XXXVIII, 392 p. 69 illus., 43 illus. in color.
Keywords: This book highlights various dimensions of human habitats in 21st Century India. The human habitats in the country are marked by perceptible inequality in social and economic spheres. This is occurring in tandem with rapid socio-economic transformation across both rural and urban landscapes. There is a plurality of transformative characteristics in terms of social and economic classes, gender and space. Inequality in access to natural resources such as land and water is still a big factor in socio-economic differentiation in rural habitats. This constructs a pedestal of unequal opportunities and access to basic human necessities such as healthcare, education, potable water and sanitation. Human habitats experiencing socio-spatial segregation and exclusion based on caste, community and gender are detrimental in formation of a civil society and its sustainability in long terms. The ideal situation for this would be formation of an inclusive society that celebrates age old socio-culturaldiversities, reduces inequalities and reveres composite culture.